The Interchange of Sign Transformation between Locality and Universality in the Iraqi Theatre, "Romeo and Juliet in Baghdad Show" - A Model (Al-Academy, 2018)
The research deals with the interchange of the sign transformed from the universal to the local in the theatrical show through the direction processing in the production of a communicative artistic discourse and message, thus making the process of reading the speech and recognizing it by taking into account the cultural differences, customs and local rituals of each country, region, or area. The problem of the research was focused on answering the following question: What are the requirements for the sign in terms of its transformation between the universality and locality in the read-out? The importance of research is to determine the requirements and mechanisms used in the follow-up of the sign in terms of its interchangeability and transformation between universality and locality in the Iraqi theater in addition to determining the subjective limits of the research in addressing the theatrical show, which employed the sign and its transformations and the interchangeability of these transformations as a performance in (2012) and then the definition of terms and the procedural definition. The theoretical framework is divided into two sections the first of which deals with the concept of the sign, its essence, and its transformation, in addition to the method of work and the sign interchange between one culture and another. The second section: the aesthetic work of the interchangeability of the sign transformation in the read-out and the effect that the shifting sign leaves between the local and the local on the spectator. The researchers, through the theoretical framework, reached a number of indicators that were applied to the selected sample through the research procedures. The research procedures included the research community and its limitations and took a model of a selected sample from the research community to see the possibility of operating the theoretical framework indicators on this sample, (Romeo and Juliet in Baghdad). At the end of the research, the researchers reached the results, including that the theatrical show is to employ what can be employed from the arts, cultures, sciences and modern international or local techniques in order to produce a speech based on the harmony of thought and form to produce a content of a unique nature, taking into account the local culture of each region, and way of adapting the international texts and shows to the transformations and sign interchangeability that are appropriate to that culture in order to create the greatest possible impact on the recipient. At the end, the research ends with the conclusions, recommendations and sources